The Formation of a Dry‐Belt in the North Side of Central Himalaya Mountains. Issue 5 (13th March 2019) - Wang, Yan; Yang, Kun; Zhou, Xu; Wang, Binbin; Chen, Deliang; Lu, Hui; Lin, Changgui; Zhang, Fuqing
Abstract: South Asian monsoon crosses the Himalayan Mountains (HMs) and brings moisture for precipitations in the South Tibetan Plateau. A distinct dry‐belt was found in the north of the central HM region, where there are the highest and steepest mountains in the world. Through in situ and remote‐sensing observations and convection‐permitting numerical experiments, the current study demonstrates that the formation of the dry‐belt is mainly due to the depletion of water vapor when the monsoonal flow climbs the steep south slope of the HMs. The foehn phenomenon is notable over the north slope of the HMs, but the hot and dry downslope flow does not significantly reduce the amount of the precipitation; instead, it can delay the peak of the diurnal precipitation in the north side of the HMs. Plain Language Summary: The central Himalaya Mountains (HMs) possess the highest and steepest mountains. Recent in situ and remote‐sensing observations show a dry‐belt in the north side of the central HMs. Although it is plausible to speculate that the dry‐belt results from the foehn wind on the leeside of the HMs, this study shows that the formation of the dry‐belt is mainly caused by the drastic depletion of water vapor along the south slope of central HMs. The foehn wind mainly delays the diurnal peak of precipitation but hardly reduces the amount of precipitation. Key Points: A distinct dry‐belt was found in the north of the central Himalaya Mountains The dry‐belt is mainly due to the depletion of water vapor over the south slope of the Himalaya Mountains The foehn wind can postpone the diurnal cycle of the precipitation in the north side of the Himalaya Mountains